Effects of Different Doses of Exercise on Inflammation Markers Among Adolescents with Overweight/Obesity: Hepafit Study - Garcia-Hermoso, A (Endocrine Society, 2022)
Propose: Obesity-related metabolic risk factors in adolescents who are overweight/obese may be associated with systemic low-grade inflammation; therefore, we investigated whether 6 months of exercise training altered markers of inflammation. Methods: Secondary analyses of a randomized controlled exercise-based intervention trial (September 2017-December 2018). Adolescents aged 11 to 17 years (Tanner stage II-V), 70% girls, with a body mass index z-score at or above the 85th percentile, and/or with excess of adiposity (body fat ≥ 30%). The participants were randomly assigned to the following 4 groups for 6 months: (1) standard physical education lessons, as a control (CTRL); (2) high-intensity physical education class (HIPE); (3) low-to-moderate intensity physical education class (LIPE); (4) a combined group (PLUS). Inflammatory markers and immune molecules including chemokines, cytokines, and growth factors (n = 65 biomarkers) were determined by cytokine antibody array. Results: Of the 120 randomly assigned participants, 95 were included in the analysis. Considering these 22 proteins, the LIPE group shows statistical significance in 9 proteins with log-fold change (logFC) and P < 0.05 (in BLC, eotaxin, fibroblast growth factor-6 [FGF-6], GCP-2, I-309, IGFBP-4, MCP-4, NAP-2, and PARC), followed by the PLUS group in 9 proteins (BLC, pro-epidermal growth factor, eotaxin, FGF-6, MCP-4, NAP-2, osteopontin, PARC, and RANTES), the HIPE group in 7 proteins (FGF-4, FGF-7, GCP-2, IGF-1, IGFBP-1, IGFBP-4, and MIP-1 delta), and the CTRL group in 6 proteins (FGF-4, IP-10, Leptin, MCP-1, MIG, and MIP-1 delta). However, subanalysis performed to detect differentially expressed proteins at baseline and after intervention, with significance at an adjusted P value ≤ 0.05 and absolute log fold-change (logFC) ≥ 1.0, showed 3 downregulated proteins in the LIPE group (BLC(logFC) = 1.27, eotaxin(logFC) = 1.18, and MCP-4(logFC) = 1.14), and 4 proteins in the HIPE group (BLC(logFC) = 1.45, FGF-6(logFC) = 1.20, MCP-4(logFC) = 1.50, and PARC(logFC) = 1.33), supporting that the changes we observed in the exercise groups were not time-related changes but occurred in response to exercise. Conclusions: Implementing a 6-month physical exercise program in overweight/obese adolescents, based on LIPE and PLUS groups, significantly change several circulating inflammatory levels. Interventions involving supervised physical exercise may reduce the associated effects of systemic low-grade inflammation, thus preventing the development of obesity-related metabolic diseases in adolescents with overweight/obesity. © 2022 The Author(s) 2022.